AVALIAÇÃO DA IMPLEMENTAÇÃO DOS DIAGNÓSTICOS DE ENFERMAGEM A PACIENTES NO PERIOPERATÓRIO DE CIRURGIA CARDÍACA. - OLIVEIRA, Bruna da Silva (2019)
The cardiovascular diseases constitutes the main cause of morbidity and mortality in many countries. The treatment of these diseases can be clinic or surgical and has as goal reestablish the heart functional capacity. For being complex interventions, the cardiac surgeries require a proper approach in all perioperative phases. In this context, the Nursing should use a proper method of work, the Nursing Process. It is highlighted between its steps the nursing diagnosis which are trials that provide criteria for assistance evaluation and orientate the care. It objectified evaluate the implementation of the nursing diagnosis to patients in the perioperative of cardiac surgery. It is a retrospective documentary search fulfilled in a university hospital from Sao Luis – Maranhão starting the medical records data of adult patients who performed a Myocardium Revascularization surgery and/or Valvar Surgery between 2013 and 2016, with sample of 304 medical records. The nursing diagnosis identified were analyzed to the Conceptual Reference of Taxonomy II from NANDA – I. The project was forwarded to the Research Ethics Committee form the same institution, getting favorable seems number 2,510.416/2018. It prevailed in the search men with 57,8 years old, brown, in stable union, uncompleted elementary school and retired. Among the clinic data, the cardiopathy more prevalent was the coronary arterial disease, followed by the mitral valve diseases. Most of the people did the Myocardium Revascularization Surgery. About the nursing diagnosis, they were not found in the analyzed period, records in the preoperative phase in the infirmaries and in the intraoperative phase, in the surgery center; therefore, it was not possible the implementation evaluation since this stage wasn´t implanted in the cited sectors. The found preoperative diagnosis limited to the elaborated ones from the cardiological Intensive Care Unit, sector that predominated in relation to the diagnosis found in the post-operative. Between the second semester of 2014 and the first semester of 2016, the diagnosis was elaborated in an electronic way, with no possibility of printing and registering in paper records, making it impossible the implementation analysis, being this case a study limitation. The most usual diagnosis in the pre-operative were Impaired Tissues and Skin Integrity; Interrupted Family Process; Poor Knowledge; Risk for Infection and Decreased Cardiac Output. In the post-operative, most people presented Impaired Tissues and Skin Integrity, Impaired Spontaneous Ventilation, Impaired Physical Mobility, Risk for Infection, Risk for Inhalation, Risk of Imbalance in the Liquid Volume and Risk of Bleeding. It evidenced diagnosis with uncompleted framing or outdated in relation to the Taxonomy II from NANDA-I. It is emphasized the importance of the diagnosis framing based on evidences that reflect on the consistent clinic reasoning by the nurses who work in the care area in all perioperative stages of the cardiac surgery, ensuring a safety, effective and individual care.